RESULTS OF SURGICAL TREATMENT OF PATIENTS WITH ANKLE FRACTURES - Ахтамов Азим Аъзамович (Web of Journals Publishing, 2024)
Ankle fractures are one of the most common injuries of the musculoskeletal system and account for 20-24% of all skeletal injuries and 40-60% of tibial fractures; 60-80% of ankle fractures are unstable and are accompanied by confusion of fragments, dislocations and subluxations of the foot. [1,2,3,5].